Collision of Royal Law and local fueros in the process of the Spanish state formation in XVI century on the example of the Antonio Perez case - Elena Kalínina (Ибероамериканские тетради)
In this article, the Author uses the concrete case of Antonio Perez, the ex-secretary of the king Philip II of Spain, to demonstrate the course of the Spanish state formation and the integration of the Law and State with its problems and contradictions. The object of this study is to research the mentioned process in theory and in reality, because they are different. In theory, the process of the State formation comes to its end in the epoch of the Catholic Monarchs, Ferdinand and Isabella governing. Later, in the epoch of Charles V, Holy Roman Emperor, Spain was the Empire yet. However, in the epoch of Philip II the unity and integrity of the new sate are in danger, because the case of Antonio Peres demonstrates that customary law as fueros, privileges and time-honoured traditions are able to survive the political and legal processes.